Enhancing market segmentation with GloMIP's Impact Opportunities Portal - Lenaerts, Bert; Paguirigan, Neale Marvin; Demont, Matty (CGIAR System Organization, 2024)
The GloMIP Impact Opportunities Portal helps analyse over 200 development and crop production indicators across the five CGIAR Impact Areas, three scaling levels (national, national-crop, and market segment), 46 crops (including 20 CGIAR crops), 170 countries, and 23 grouping levels. Market segmentation can benefit from evidence generated at scale through the tool in three main ways. First, the portal allows prioritizing market segments based on selected indicators, either individually or combined in an index. Second, the portal calculates the split between segmented and unsegmented opportunities, showing what portion of regional impact opportunities the market segments cover. This can help ensure that market segmentation aligns with global needs and identify any missing market segments. Third, the portal aids in market segmentation by providing national cropping area, yield, and price data from FAO, which can act as building blocks for new market segments.